PERAN MUSIK UNTUK TERAPI ANAK DENGAN SINDROM DOWN - Yelvi Levani; Ervalinda Dzakirah Fahriyah; Anggie Novtania Hasyim; Andhyn Zakiyahartanti; Muammar Qadhafi; Muhammad Helmi Naufal (PROCEEDING UMSURABAYA, 2023)
Down syndrome is a genetic disease caused by the failure of the 21st chromosome to separate itself during division. It is estimated that 1 in 600 births is a Down Syndrome baby. This incident is mostly caused by the age of the mother. If the mother's age increases during pregnancy, the incidence of the birth of a child with Down syndrome also increases. The phenotype of each patient with Down Syndrome can be different, generally patients have physical disorders and delays in mental development. There are various ways that are likely to improve cognitive function in children with Down syndrome, including using early interventions that target the development of social skills. One of them is with music intervention. The results of previous research indicate that learning music can help develop the mentality of children who are initially shy to become skilled.Keywords: Down Syndrome, rehabilitation role, music